The Effectiveness of Mediation in Inheritance Law Disputes is Linked to Perma No. 1 of 2016 at the Karawang Religious Court - Dini Nurfalah; Amaliya, Lia; Abas, Muhamad (Journal of Law, Politic and Humanities, 2024)
Mediation as an alternative dispute resolution mechanism outside of court has long been used in various business, environmental, labor, land, housing, and so on cases that are fast, effective and efficient. Mediation comes from the English "Mediation" or "mediation", namely resolving disputes by mediation. Inheritance issues are also a concern because they relate to social responsibilities entrusted to heirs. The formulation of the problem to be studied in the following research is the authority of the mediator judge at the Karawang Religious Court in resolving inheritance case disputes, how effective the mediator is in handling inheritance cases in Number: 2222/Pdt.G/2022/ PA. Karawang. And what are the obstacles that hinder the mediation process at the Karawang Religious Court? In this research the author uses an empirical juridical approach. The reason the author uses this method is because the main data used is primary data, namely in the form of data obtained based on field studies and supporting data is secondary data, namely in the form of data obtained based on literature studies, statutory regulations, legal principles relating to the problem that the author will discuss. To overcome these obstacles, the Karawang Religious Court can make efforts such as increasing public awareness about the benefits of mediation, increasing the number and quality of mediators, allocating sufficient resources for the mediation process, building trust from the parties concerned.